Sustainable competitive advantage strategy in hospital industry to response policy change in Indonesia: A narrative review - Lestari, Marselli Widya; Surjoputro, Antono; Sriatmi, Ayun (Public Health of Indonesia, 2021)
In response to policy changes, the hospital as an organization is expected to establish a strategy to stay afloat in business competition. However, the health industry, especially hospitals, has certain determinants that are different from other industries. This article is a literature review that focuses on business strategy management, namely sustainable competitive advantage in the hospital industry. This review is aimed at managers nowadays in building and maintaining their hospital positions. In conclusion, changes in strategy can be made specifically according to the type of hospital and positioning results.